POLYCHLORINATED BIPHENYLS IN FISH (HETEROTIS NILOTICUS) IN IGBOKODA RIVER, ONDO STATE NIGERIA - Ediagbonya, T. Faraday; Uche, Joseph I.; Arogbola, Daniel O. (FUDMA JOURNAL OF SCIENCES, 2024)
Polychlorinated biphenyls are composed of 209 possible chlorinated compounds or congeners with lipophilic properties. They are bioaccumulative, persistent pollutants that have been related to a variety of negative human health effects, including cancer. Humans can be exposed to PCBs by eating contaminated foods such as fish, pig, and dairy products. The purpose of this study was to quantify PCB contents in heterotis niloticus using an electron capture detector in gas chromatography (GC-ECD). The presence of PCBs in the fish's head, tail, and centre was determined. The average total PCB concentration was 4.27g/g in the centre, 6.43g/g in the tail, and 2.42g/g in the head. PCBs 8, 18, 28, 44, 156, and 170 were discovered in the fish's head, middle, and tail, except for PCB 8, which was not found in either the head or the tail. The concentration of PCBs in this study found that, except for the middle, which had a mean value of 0.01, there was no PCB8 in the fish's head or tail. The least amount of total PCB was found in the fish head, while the highest concentration was detected in the tail. Except for PCB8, which was not calculated since it only occurred in one location of the fish, the various PCB homologs showed statistical spatial variations. According to the distribution of PCB homologs in fish samples, triPCBs were present in the majority of fish components, whereas tetraPCBs were found in the middle and tail at low levels.
Keywords: Fish; Polychlorinated biphenyls; Igbokoda river; Pollution